City marketing between a theoretical reflection and a practical realization - Jiri Jezek (European Regional Science Association (ERSA), 2010)
The paper deals with theoretical and application problems of city marketing. It is based on a series of researches which have been worked mainly in the Czech Republic, Slovak Republic, Austria, Germany and in the Netherlands. At the same time it points out the specific conditions and sometimes also different interpretations of city marketing in the countries mentioned above. The paper also points the series of discrepancies between theoretical hypothesis and practical realization of city marketing and in its final part it proposes a future of city marketing.
Keywords: 330; town marketing; implementation; strategy of the municipal policy; Czech Republic; Austria